Respon Perkecambahan Benih Bawang Merah (Allium ascalonicum L.) dengan Perlakuan Rendaman Cendawan Beauveria bassiana (Balsamo) Vuillemin: Response of Germination of Shallot Seeds (Allium ascalonicum L.) with Immersion Treatment of Beauveria bassiana (Balsamo) Vuillemin - Nasuiton, Lita; Riduan Sembiring; Dedi Holden Simbolon; Magdalena Saragih; Swati Sembiring; Donatus Dahang; Rifa Diah Valahsya Sembiring; Rico Taruna Siregar; M. Fauzan Eren; Yolanda Febrima Tarigan (UIR Press, 2026)
Background: The fungus Beauveria bassiana (Balsamo) Vuill is an entomopathogenic fungus widely used as a biological control agent against insect pests in plantation, food, and horticultural crops. Beyond its role as a biocontrol agent, B. bassiana has also been reported to enhance seed germination and early growth of shallot plants. Objective: his study aimed to determine the germination response of shallot seeds (Allium ascalonicum L.) to seed soaking treatment using B. bassiana at varying concentrations and soaking durations. Methods: TA field experiment was conducted from January to March 2026 using a factorial Randomized Complete Block Design (RCBD) with two factors: concentration (V) and soaking duration (P). Parameters observed included germination percentage, germination rate, shoot height, leaf number, leaf length, root length. Results: The results showed that the concentration of 15 ml/L (V3) gave the best effect on all parameters, while the soaking duration of 9 hours (P1) was optimal and not significantly different from longer soaking durations. The combination treatment of V3P1 (15 ml/L + 9 hours) produced the highest germination percentage (35% at 25 days after planting), the best germination speed (11.3 days), as well as superior shoot height and root length. The ability of B. bassiana to enhance growth is thought to be due to the production of phytohormones such as auxin and gibberellin. Conclusions: In conclusion, soaking shallot seeds in a suspension of B. bassiana at a concentration of 15 ml/L for 9 hours is recommended to improve seed viability and growth